Scale Effect on Hydraulic Properties of Pore-Fissure Deep Rock Formations and Its Importance for the Mining Shaft-Sinking Process - Maciej Pikuła; Krzysztof Chudy; Magdalena Worsa-Kozak; Mariusz Czop (Energies, 2023)
The problem of hydraulic parameters estimation lies in the depth: the deeper the rock formation, the more expensive and difficult the field tests and samples acquisition, and the more challenging the technical issues. The article assesses the Triassic sandstone’s drainage potential at the stage of shaft sinking. It focuses on parameter analysis in varied scales, from drill-core sample laboratory testing, through a single well drawing test, to long-term pumping and recovery tests in the well with observation piezometers. The obtained results are compared to the values estimated in the past using different methods. Finally, the paper states whether it is reliable to forecast pore-fissure sandstone drainage potential based only on core samples’ laboratory tests. This research proved that lab tests underestimate pore-fissure rocks’ hydraulic parameters (mean hydraulic conductivity k = 9.79 × 10<semantics>−8</semantics> m/s) tenfold more than long-term pumping tests (mean k = 4.45 × 10<semantics>−7</semantics> m/s). However, it can be concluded that the group of so-called “witness samples”, 10% of all core samples with a top value of the hydraulic conductivity tested in the laboratory, can be representative of the aquifer and comparable to the values obtained in pumping tests. With this in mind, we recommend using the highest values of hydrogeological parameters from laboratory tests based on the worst-case scenario. Therefore, it is possible to forecast inflows to the shafts reliably. This methodology is recommended only for rocks of porous and pore-fissure character.